MACARANGIN, A GERANYLATED FLAVONOID AND ANTICANCER ACTIVE COMPOUND ISOLATED FROM ETHYL ACETAT FRACTION OF Macaranga gigantifolia LEAVES - Darmawan, Akhmad; Suwarso, Wahyudi P.; Kosela, Soleh; Kardono, Leonardus B.S.; Fajriah, Sofa (INDONESIAN JOURNAL OF PHARMACY, 2015)
Macaranga known locally as mahang-mahangan has uniquely ecological function, and also became a part of traditional medicine in Indonesia. Macaranga genus also known as a sources of terpenoid and phenolic (flavonoid) compounds which have biological activity as antioxidant and anticancer (cytotoxicity).There are few phytochemical investigations have been done on M. gigantifolia species. As a part of our continuing research of isolation anticancer compound from natural product, a geranylated flavonoid compound (macarangin) has been isolated from ethyl acetate fraction of Macaranga gigantifolia leaves using chromatography methods. The isolated compund (isolat MG) was elucidated to gain the chemical structure based on spectroscopic data (LC-MS and FT-NMR). Cytotoxicity test of this compound was tested against MCF 7 cell lines, showed that macarangin has a potential activity with IC50 value 119.12Î¼g/mL.Â Key words: Macarangin, geranylatedÂ  flavonoid, Macaranga gigantifolia, MCF 7 cell lines.